Approach to the application of evolutionary game theory in the area of entrepreneurship [Acercamiento a la aplicación de la teoría de juegos evolutiva en el área de emprendimiento] (2016)
The implementation of concepts and theories from evolutionary biology in the economic behavior and business sciences has been gaining research significance. The aim of this paper, through literature review, is doing an approach to understanding the scope of evolutionary game theory (EGT) in the entrepreneurship area. It is observed that EGT is a useful tool for understanding the entrepreneurship process, considering elements of complexity, allowing to make analogies that support the entrepreneurship analysis and entrepreneurial behavior characterization.